Entrepreneurial Intentions among Indigenous Dayak in Sarawak, Malaysia : An Assessment of Personality Traits and Social Learning - Tateh, 0.; Latip, H.A; Dayang Affizzah, Awang Marikan (The Macrotheme Review, 2014)
This study examines two aspects that have major influence to entrepreneurship as widely described in literature: the personality traits and social learning. The interest of study was on the indigenous Dayak in East Sarawak Malaysia. With the use of quantitative methods for data collection and analysis, the impacts of personality traits and social learning of the respondents on development of their entrepreneurial intentions were investigated. The correlation analysis indicated that the respondents’ entrepreneurial intentions are positively correlated to their personality traits (risk taking propensity, innovativeness and tolerance of ambiguity), and social learning (knowledge and experience, family upbringing). This study therefore articulates the present view of Dayak in Sarawak about their entrepreneurial intention, and its implication to indigenous entrepreneurship development.